2017
DOI: 10.1038/nature21676
|View full text |Cite|
|
Sign up to set email alerts
|

Effective combinatorial immunotherapy for castration-resistant prostate cancer

Abstract: A significant fraction of advanced prostate cancer (PCa) patients treated with androgen deprivation therapy (ADT) experience relapse with relentless progression to lethal metastatic castration-resistant prostate cancer (mCRPC)1. Immune checkpoint blockade (ICB) using antibodies against cytotoxic-T-lymphocyte-associated protein 4 (CTLA4) or programmed cell death 1/programmed cell death 1 ligand 1 (PD1/PD-L1) generates durable therapeutic responses in a significant subset of patients across a variety of cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
389
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 442 publications
(422 citation statements)
references
References 45 publications
(60 reference statements)
16
389
1
1
Order By: Relevance
“…Robust synergistic responses were obtained in a prostate cancer mouse model with the combination of ICB and the multikinase inhibitor cabozantinib or the phosphoinositide 3-kinase (PI3K)/ mTOR dual inhibitor BEZ235 (56). Both cabozantinib and BEZ235 diminish MDSCs and enhance ICB through inhibition of PI3K signaling and downregulation of cytokines responsible for immunosuppression-related gene expression (56). In renal cell carcinoma (RCC), antiangiogenic agents are evaluated in combination with ICB.…”
Section: Other Type Of Tumorsmentioning
confidence: 99%
“…Robust synergistic responses were obtained in a prostate cancer mouse model with the combination of ICB and the multikinase inhibitor cabozantinib or the phosphoinositide 3-kinase (PI3K)/ mTOR dual inhibitor BEZ235 (56). Both cabozantinib and BEZ235 diminish MDSCs and enhance ICB through inhibition of PI3K signaling and downregulation of cytokines responsible for immunosuppression-related gene expression (56). In renal cell carcinoma (RCC), antiangiogenic agents are evaluated in combination with ICB.…”
Section: Other Type Of Tumorsmentioning
confidence: 99%
“…Thus, it may be that the transient nature of the increase in cytokines due to PD-1 antibody treatment could be due to development of immune inhibitory mechanisms other than through the PD-1 immune checkpoint axis. This concept is supported by other studies showing only modest clinical effectiveness of checkpoint blockade treatment in a prostate cancer model, but a robust synergistic response when checkpoint blockade treatment was combined with kinase-inhibitory treatment targeting infiltration by myeloid-derived suppressor cells [33]. A separate study also demonstrated alternative inhibitory mechanisms, such as IL-17 stimulation of intratumoral neutrophil infiltration, as contributors to PD-1 blockade resistance by lung cancer [34].…”
Section: Discussionmentioning
confidence: 60%
“…In recent years, cancer immunotherapy has drawn much attention due to its remarkable curative effects . Immune cells, including T cells, NK cells, and DCs play a key role in antitumor immune responses and cancer immunotherapy.…”
Section: Cancer Immunotherapies By Targeting B Cellsmentioning
confidence: 94%